Stages of smoking cessation among Malaysian adults: findings from National Health Morbidity Survey 2006 - Lim, Kuang Hock; Ibrahim, Normala; Mohd Ghazali, Sumarni; Kee, Chee Cheong; Lim, Kuang Kay; Chan, Ying Ying; Teh, Chien Huey; Tee, Eng Ong; Lai, Wai Yee; Nik Mohamed, Mohamad Haniki; Mohd Sidik, Sherina (Asian Pacific Education Press Ltd., 2013)
Increasing the rate of smoking cessation will reduce the burden of diseases related to smoking, including cancer. Understanding the process of smoking cessation is a pre-requisite to planning and developing effective programs to enhance the rate of smoking cessation.The aims of the study were to determine the demographic distribution of smokers across the initial stages of smoking cessation (the pre-contemplation and contemplation stages) and to identify the predictors of smoking cessation among Malaysian adult smokers. Data were extracted from a population-based, cross-sectional survey carried out from April 2006 to July 2006. The distribution of 2,716,743 current smokers across the pre-contemplation stage (no intention to quit smoking in the next six months) or contemplation stage (intended to quit smoking in the next six months) was described. Multivariable logistic regression analysis was used to examine the relationship between socio-demographic variables and the stages of smoking cessation. Of the 2,716,743 current smokers, approximately 30% and 70% were in the pre-contemplative and contemplative stages of smoking cessation respectively. Multivariable analysis showed that male gender, low education level, older age group, married and those from higher income group and number of cigarettes smoked were associated with higher likelihood of pre-contemplation to cease smoking in the next six months. The majority of current smokers in Malaysia were in the contemplative stage of smoking cessation. Specific interventions should be implemented to ensure the pre-contemplative smokers proceed to the contemplative stage and eventually to the preparation stage.